Bodies in context : a comparative study of early childhood education in New Zealand and Japan : a thesis presented in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Social Anthropology at Massey University, Albany, New Zealand - Burke, Rachael Sarah (Massey University, 2013)
Early childhood education in both New Zealand and Japan is increasingly being seen as an essential experience for children as evidenced by the growth of the early childhood sector and lively political debate. In New Zealand, the bi-cultural curriculum makes a clear commitment to supporting ethnic diversity in the classroom. While Japanese centres have been categorised as culturally homogeneous in the past, focus is now turning to accommodating children from a variety of backgrounds. In both countries less attention has been paid to the latent cultural assumptions underpinning children’s, families and teachers’ experiences of early childhood education. Using Tobin et al.’s (1989, 2009) PSC3 methodology to stimulate a multi-vocal text through the use of videotape, this thesis examines how early childhood settings in New Zealand and Japan incorporate these implicit beliefs into pedagogy and practice. This study suggests that implicit cultural practices not only shape many of the interactions of the early childhood context, but also many of these practices often go unnoticed or unrecognised as culturally informed. Using visual methods to reflect on comparative material is a powerful way to reveal hidden cultural assumptions. The video-cued method works to collapse and accelerate the traditional ethnographic fieldwork process as the videos provide a focus for discussion, and help reduce the kind of ambiguity that can occur when interviewing across cultural contexts. Through the layers of dialogue stimulated by the videos, children’s bodies emerged as the locus of the work. Although the body was once neglected as an object of scholarly study, it has now become a significant site for anthropological analysis. Inspired by Foucault (1995) scholars came to acknowledge that the body is not only socially and culturally produced, but historically situated within conceptions of society and nature. Using the theories of Foucault (1995), Douglas (1966, 1996) and Mauss (1973) as a framework, this study argues that the ways in which children’s bodies are constructed, protected, disciplined and challenged provide a useful lens through which to examine unseen cultural practices. As early childhood settings become more diverse, it is hoped this study will provide points for reflection and offer practical applications for teachers. With this aim in mind, the thesis incorporates film, qualitative interviews, vignettes and personal reflections to make the work accessible to a wider audience than traditional academic writing.
Keywords: Preschool education; Early childhood education; Child rearing; Human body; Children's bodies; Social aspects; Comparative education; New Zealand; Japan; Social anthropology